Method for preparing copper heat dissipation material through electrolytic copper powder injection molding

Through technical means such as electrolytic copper powder grinding, powder refining, injection molding, atmospheric sintering + aging treatment + pressurized sintering and stress removal annealing, the problems of low utilization rate of heat dissipation materials, complex structure and difficult preparation, and high production costs are solved, and the thermal conductivity and electrical conductivity of copper heat dissipation materials are synergistically improved, and the strength and ductility of the material are significantly improved.

CN119819927AActive Publication Date: 2025-04-15UNIV OF SCI & TECH BEIJING +1
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411927681.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-15
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

In the prior art, the heat dissipation materials have low utilization rate, complex structure and difficult to prepare, and high production costs. If the addition of alloy particles is used to improve thermal and electrical conductivity, there will be technical problems such as the inability to improve the performance of the two, and the performance of the two cannot be improved synergistically, accompanied by strong plasticity mismatch, the inability to prepare complex-shaped copper parts, and the difficulty of operation.

Method used

Through various technical means such as electrolytic copper powder grinding, powder refining, injection molding, atmospheric sintering + aging treatment + pressurized sintering and stress removal annealing, copper heat dissipation materials with high strength, high thermal conductivity and excellent ductility are prepared.

Benefits of technology

The thermal conductivity and electrical conductivity of copper heat dissipation materials have been achieved, and the strength and ductility of the materials have been significantly improved. It can prepare copper parts in complex shapes, which are simple to operate, low cost, short process and high efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119819927A_ABST
    Figure CN119819927A_ABST
Patent Text Reader

Abstract

The invention provides a method for preparing a copper heat dissipation material through injection molding of electrolytic copper powder, and relates to the technical field of powder metallurgy. The method comprises the following steps: obtaining electrolytic copper powder subjected to grinding and crushing treatment; electrolytic copper powder, alloy powder and a wax-based binder are subjected to high-temperature and high-speed banburying, and high-purity feed is obtained; carrying out high-purity feed injection molding to obtain a green body part; then the green body part is subjected to solvent degreasing and heating degreasing, and a sample subjected to thermal degreasing is obtained; and sequentially carrying out hydrogen atmosphere normal pressure sintering, solid solution aging treatment and pressure sintering on the sample subjected to thermal desorption, and finally carrying out annealing stress relief treatment to obtain the copper heat dissipation material. The high purity, large specific surface area, easy forming, high sintering activity and excellent electric conduction and heat conduction performance of the electrolytic copper powder are fully played, the material has high strength and excellent ductility through solid solution aging treatment, preparation of the high-heat-conduction large-size complex-structure copper heat dissipation material is achieved, the preparation process is stable, the price is low, and the method is suitable for industrial production. And the method is more suitable for mass production and use.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of powder metallurgy, in particular to a method for preparing copper heat dissipation material by injection molding of electrolytic copper powder. Background Art

[0002] Copper is widely used in modern national economic construction and people's daily life. It is also indispensable in cutting-edge technologies such as high-energy physics, superconducting technology, and cryogenic engineering. Copper has excellent properties: high electrical and thermal conductivity, anti-magnetism, high corrosion resistance, good processing deformation ability, high mechanical properties and good plasticity.

[0003] Electrolytic copper powder is widely used in diamond tools, carbon brushes, friction plates, etc. due to its high purity, developed dendritic morphology, easy molding, high sintering strength, and excellent electrical and thermal conductivity. However, due to the low bulk density of electrolytic copper powder, it greatly increases the difficulty of downstream customers in the application process, because a small bulk density means a larger volume under a certain mass, which greatly limits the wide application of electrolytic copper powder.

[0004] The advantage of powder injection molding is that it can form complex metal parts in large quantities, and the density of each part of the product is uniform and has excellent performance. Therefore, how to give full play to the characteristics of high sintering activity of electrolytic copper and excellent sintering performance of parts has put forward higher requirements for existing technicians.

[0005] Chinese patent CN118926519A discloses a nanoporous copper heat dissipation material based on a combination of a composite copper mesh and surface modification and a preparation method thereof. The method compacts a copper salt mixture to form a loose structure, lays multiple layers of copper meshes of different mesh sizes to form a composite gradient copper mesh, presses and forms a pressed sheet, and then chemically etches it. Obviously, the heat dissipation material has a complex structure, a long preparation process, high production costs, and low efficiency.

[0006] Chinese patent CN114131018A discloses a method for preparing a heat dissipation material of a pressed copper nano-stacked bed. This method requires the use of four mixed particles. The arrangement method and copper mesh structure setting increase the cost. The cold pressing method and vacuum sintering make the prepared heat dissipation material a porous structure material with poor electrical conductivity and uneven thermal conductivity. Chinese patent CN113458396A discloses a method for preparing a copper-based metal honeycomb heat dissipation material. It also uses the structure of the heat dissipation material to improve the heat dissipation performance; however, it needs to remove the carbon remaining from the carbonization of the binder by sintering and oxidation in an oxygen atmosphere furnace, which will make the thermal degreasing efficiency of the heat dissipation material low. If excessive removal is done, the heat dissipation material will be oxidized and the heat dissipation performance will be poor.

[0007] Chinese patent CN111455373A discloses a method for preparing a high thermal conductivity and high temperature resistant composite copper alloy heat dissipation material. The method requires raw material selection, powder mixing prefabrication, surface cladding, and mechanical processing. However, the raw material selection adds a lot of hard particles, which will increase the strength and hardness of the prepared heat dissipation material, while reducing the plasticity; therefore, thermal stress during mechanical processing may cause cracks or fractures in the material. Summary of the invention

[0008] In order to solve the problems of low utilization rate of heat dissipation materials, complex structure and difficult preparation, and high production cost in the prior art, if alloy particles are added to improve thermal conductivity and electrical conductivity, the two properties cannot be improved synergistically, accompanied by mismatch of strength and plasticity, inability to prepare copper parts with complex shapes, and difficulty in operation, etc., the present invention proposes a method for preparing copper heat dissipation materials by electrolytic copper powder injection molding that can solve the above problems. The technical solution is as follows:

[0009] A method for preparing a copper heat dissipation material by electrolytic copper powder injection molding, the method for preparing a copper heat dissipation material by electrolytic copper powder injection molding comprises the following steps:

[0010] S1. Grinding and crushing of electrolytic copper powder: weighing electrolytic copper powder, crushing the electrolytic copper powder particles by ultrafine mechanical impact mill, and obtaining ground and crushed electrolytic copper powder;

[0011] S2, powder mixing: the electrolytic copper powder and alloy powder ground and crushed in S1 are mixed with wax-based binder at high temperature and high speed to obtain high-purity feed;

[0012] S3, injection molding: S2 high-purity feed is injection molded to obtain a green part with no defects, no deformation and uniform composition; then the green part is subjected to catalytic degreasing and thermal degreasing to obtain a thermally degreased sample;

[0013] S4, normal pressure sintering + aging treatment + hot isostatic pressing sintering: the sample after thermal stripping in S3 is subjected to normal pressure sintering in hydrogen atmosphere + aging treatment + pressure sintering in nitrogen atmosphere in sequence to obtain the sintered copper heat dissipation material;

[0014] S5, annealing: The copper heat dissipation material after sintering in S4 is subjected to stress relief annealing to finally obtain a copper heat dissipation material with high strength, high thermal conductivity and excellent ductility.

[0015] Optionally, the particle size D50 of the S1 electrolytic copper powder is 15-20µm.

[0016] Optionally, the experimental parameters of S1 ultrafine mechanical impact mill are: inlet air volume 200-300m 3 / h, mill speed 2500-3000r / min, classification impeller speed 1500-2500r / min, feed rate 100-200g / min, after 2-4h of high-speed powder treatment, 10-15µm powder is screened out, the alloy powder is ZrCuAlNi, and its mass fraction is 1.5-3.0%.

[0017] Optionally, the mass fraction of microcrystalline wax in the wax-based binder in S2 is 50-70%, the mass fraction of polyethylene is 15-25%, the mass fraction of polypropylene is 10-15%, the mass fraction of ethylene-vinyl acetate copolymer is 10-15%, and the mass fraction of vinyl bisstearamide is 5-10%; argon or nitrogen is selected as the protective atmosphere for the mixing atmosphere.

[0018] Optionally, the temperature of the high-temperature and high-speed internal mixing in S2 is 150-170° C., the speed of the internal mixer is 25-40 rpm, and the internal mixing time is 1-2 h.

[0019] Optionally, during the S3 injection process, the injection temperature is 150-170°C, the injection pressure is 40-80bar, the injection speed is 40-60mm / s, and the mold temperature is 50-75°C; the solvent degreasing removes the main component of the binder, which is microcrystalline wax; when the thermal degreasing is performed from room temperature to 500°C, the heating rate is 1°C / min, and the temperatures are kept at 250°C, 380°C, and 550°C for 30 minutes respectively.

[0020] Optionally, S3 solvent degreasing uses trichloroethylene for solvent degreasing, dissolving at 40-55° C. for 15-30 hours to remove the main component of the binder, microcrystalline wax.

[0021] Optionally, the degreasing rate of the sample after S3 thermal degreasing is 6.0-7.8% and the density is 4.55-5.10g / cm 3 .

[0022] Optionally, in the pressureless sintering step S4, the flow rate of the hydrogen gas is ≥ 3m 3 / min, sintering temperature is 1065-1075℃, and holding time is 3-5h; during aging treatment, the aging temperature is 110-140℃, and the aging time is 30-50h. During pressure sintering, in a nitrogen atmosphere, at a pressure of 5-15bar, keep warm at a temperature of 1000-1050℃ for 2-4h.

[0023] Optionally, the annealing treatment in S5 is performed at 500-650° C., kept at this temperature for 45-80 minutes, and then cooled in the furnace under a hydrogen atmosphere.

[0024] Optionally, the S5 copper heat dissipation material has a density of 98.2-99.5%, a hardness of 105-146 HV, a tensile strength of 288.6-325.2 MPa, an elongation of 25.5-34.2%, a thermal conductivity of 352-367 W / (m·K), and an electrical conductivity of 78.8-85.6% IACS.

[0025] Compared with the prior art, the above technical solution has at least the following beneficial effects:

[0026] The above scheme, the present invention proposes a method for preparing copper heat dissipation materials by electrolytic copper powder injection molding, which can solve the problems of low utilization rate of heat dissipation materials in the prior art, complex structure and difficulty in preparation, and high production cost. If alloy particles are added to improve thermal conductivity and electrical conductivity, there will be technical problems such as the performance of the two cannot be improved synergistically, accompanied by mismatch of strength and plasticity, inability to prepare complex-shaped copper parts, and difficulty in operation.

[0027] The preparation method of the present invention prevents the high activity and easy oxidation of copper, realizes the sintering activation effect of electrolytic copper powder and the liquid phase sintering effect of low-melting copper-nickel powder, the high shape retention of plastic-based system samples and the high degreasing rate of green billets, and also adopts a variety of mechanisms to promote sintering densification, such as hydrogen atmosphere sintering and hot isostatic pressing sintering, which can significantly improve sintering densification.

[0028] The present invention uses a grinding and crushing process to disperse the agglomerated particles by utilizing the impact force generated when the particles collide with each other, and the edges and corners of the particle surfaces are ground off due to the mutual friction between the particles, so that the particle surfaces are smoother and more regular, thereby obtaining spherical or nearly spherical particles. Nearly spherical particles are more easily coated by binder particles, thereby greatly increasing the loading amount of the powder, making the density of the sintered product higher, thereby improving its thermal conductivity, electrical conductivity and mechanical properties.

[0029] The present invention enables the feed material to have good flowability through the selection of the wax-based binder, can meet the requirements of rapid prototyping of large-sized complex parts in the subsequent injection process, and can manufacture products with complex shapes and high precision requirements.

[0030] The present invention can integrate parts with complex structures through injection molding, with almost no material loss and a utilization rate of up to 98%, solving the problems of low utilization rate of radiator machining materials, complex and difficult preparation, and high production cost, and provides a new idea for the preparation of heat dissipation devices with high material costs and complex structures.

[0031] The present invention uses normal pressure sintering + aging treatment + pressure sintering to ensure that the strength-enhancing grains are fully grown and the grains are closely combined. After the solid solution aging treatment, the alloy elements form a dispersed strengthening phase in the matrix, which can significantly improve its tensile strength and ductility. Solid solution aging can refine the grains, reduce the stress concentration at the grain boundaries, make the material less likely to brittle fracture when subjected to external forces, and improve the service life of the product. The heat dissipation product may be deformed due to residual stress during subsequent processing. Solid solution aging treatment can also make the part size more stable by eliminating or reducing residual stress. For some copper alloy products, solid solution aging treatment can make the impurity elements evenly distributed, reduce lattice distortion, and thus improve the thermal conductivity and electrical conductivity of the alloy. This is of great significance in heat dissipation materials, and can make the electrical conductivity of electronic components better and reduce power loss. The sintered parts are basically fully dense, and excellent comprehensive performance is obtained to meet the use requirements of the radiator.

[0032] The present invention eliminates residual stress by performing stress relief annealing on the sintered part. Stress relief annealing can make the material's organizational structure more uniform, improve dimensional stability, and prevent the workpiece from deforming during subsequent use, ultimately obtaining a copper heat dissipation material with high strength, high thermal conductivity and excellent ductility.

[0033] The copper heat dissipation material prepared by the present invention has a density of more than 98.2%, a thermal conductivity of ≥352W / (m·K), an electrical conductivity of up to 85.6% IACS, and has excellent thermal and electrical conductivity. The copper sample has an elongation of up to 34.2%, a tensile strength of 325.2MPa, good ductility and tensile strength, is not prone to fracture and damage, and can meet the performance requirements of high thermal conductivity complex structure copper heat sinks.

[0034] In summary, compared with other traditional methods, the method of the present invention realizes the preparation of integrated needle-shaped heat dissipation materials through various mechanisms that promote sintering densification, such as powder particle size control and micro-shaping, atmosphere protection mixing, activated sintering, solution aging treatment, pressure sintering, and stress relief annealing treatment. The thermal conductivity, electrical conductivity, and strength and plasticity of the copper heat dissipation material are synergistically improved. The method is simple and easy to operate, green and environmentally friendly, low in cost, short in process, and high in efficiency. It meets the preparation requirements of high thermal conductivity, large-size, complex-structure copper heat dissipation materials, and is conducive to large-scale industrial production and promotion. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0036] Figure 1This is a process flow chart of a method for preparing copper heat dissipation material by electrolytic copper powder injection molding according to the present invention;

[0037] Figure 2 This is a microstructure diagram of a copper heat dissipation material prepared by a method for preparing a copper heat dissipation material by electrolytic copper powder injection molding according to Example 1 of the present invention;

[0038] Figure 3 This is a microstructure diagram of a copper heat dissipation material prepared by a method for preparing a copper heat dissipation material by electrolytic copper powder injection molding in Example 2 of the present invention. DETAILED DESCRIPTION

[0039] The technical solution of the present invention is described below in conjunction with the accompanying drawings.

[0040] In the embodiments of the present invention, words such as "exemplarily" and "for example" are used to indicate examples, illustrations or explanations. Any embodiment or design described as "example" in the present invention should not be interpreted as being more preferred or more advantageous than other embodiments or designs. Specifically, the use of the word "example" is intended to present the concept in a specific way. In addition, in the embodiments of the present invention, the meaning expressed by "and / or" can be both, or it can be either of the two.

[0041] In the embodiments of the present invention, "image" and "picture" may sometimes be used interchangeably. It should be noted that when the distinction between them is not emphasized, the meanings they intend to express are consistent.

[0042] In the embodiments of the present invention, sometimes a subscript such as W1 may be written as a non-subscript such as W1. When the difference is not emphasized, the meanings to be expressed are the same.

[0043] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.

[0044] A method for preparing a copper heat dissipation material by electrolytic copper powder injection molding, the method for preparing a copper heat dissipation material by electrolytic copper powder injection molding comprises the following steps:

[0045] S1. Grinding and crushing of electrolytic copper powder: weighing electrolytic copper powder, crushing the electrolytic copper powder particles by ultrafine mechanical impact mill, and obtaining ground and crushed electrolytic copper powder;

[0046] S2, powder mixing: the electrolytic copper powder and alloy powder ground and crushed in S1 are mixed with wax-based binder at high temperature and high speed to obtain high-purity feed;

[0047] S3, injection molding: S2 high-purity feed is injection molded to obtain a green part with no defects, no deformation and uniform composition; then the green part is subjected to catalytic degreasing and thermal degreasing to obtain a thermally degreased sample;

[0048] S4, normal pressure sintering + aging treatment + hot isostatic pressing sintering: the sample after thermal stripping in S3 is subjected to normal pressure sintering in hydrogen atmosphere + aging treatment + pressure sintering in nitrogen atmosphere in sequence to obtain the sintered copper heat dissipation material;

[0049] S5, annealing: The copper heat dissipation material after sintering in S4 is subjected to stress relief annealing to finally obtain a copper heat dissipation material with high strength, high thermal conductivity and excellent ductility.

[0050] In particular, the particle size D50 of S1 electrolytic copper powder is 15-20µm.

[0051] In particular, the experimental parameters of the S1 ultrafine mechanical impact mill are: inlet air volume 200-300m 3 / h, mill speed 2500-3000r / min, classification impeller speed 1500-2500r / min, feed rate 100-200g / min, after 2-4h of high-speed powder treatment, 10-15µm powder is screened out, the alloy powder is ZrCuAlNi, and its mass fraction is 1.5-3.0%.

[0052] In particular, the mass fraction of microcrystalline wax in the wax-based binder in S2 is 50-70%, the mass fraction of polyethylene is 15-25%, the mass fraction of polypropylene is 10-15%, the mass fraction of ethylene-vinyl acetate copolymer is 10-15%, and the mass fraction of vinyl bisstearamide is 5-10%; argon or nitrogen is selected as the protective atmosphere for the mixing atmosphere.

[0053] In particular, the temperature of the high-temperature and high-speed internal mixing in S2 is 150-170° C., the speed of the internal mixer is 25-40 rpm, and the internal mixing time is 1-2 h.

[0054] In particular, during the S3 injection process, the injection temperature is 150-170°C, the injection pressure is 40-80bar, the injection speed is 40-60mm / s, and the mold temperature is 50-75°C; the main component of the binder removed by solvent degreasing is microcrystalline wax; when thermal degreasing is performed from room temperature to 500°C, the heating rate is 1°C / min, and the temperatures are kept at 250°C, 380°C, and 550°C for 30 minutes respectively.

[0055] In particular, S3 solvent degreasing uses trichloroethylene for solvent degreasing, dissolving at 40-55°C for 15-30h to remove the main component of microcrystalline wax in the binder.

[0056] In particular, the degreasing rate of the S3 samples after thermal degreasing was 6.0-7.8% and the density was 4.55-5.10 g / cm 3 .

[0057] In particular, in the S4 pressureless sintering step, the flow rate of the hydrogen gas is ≥ 3m 3 / min, sintering temperature is 1065-1075℃, and holding time is 3-5h; during aging treatment, the aging temperature is 110-140℃, and the aging time is 30-50h. During pressure sintering, in a nitrogen atmosphere, at a pressure of 5-15bar, keep warm at a temperature of 1000-1050℃ for 2-4h.

[0058] In particular, the annealing treatment in S5 is performed at 500-650° C., maintained at this temperature for 45-80 minutes, and then cooled in the furnace under a hydrogen atmosphere.

[0059] In particular, the S5 copper heat dissipation material has a density of 98.2-99.5%, a hardness of 105-146HV, a tensile strength of 288.6-325.2MPa, an elongation of 25.5-34.2%, a thermal conductivity of 352-367W / (m·K), and an electrical conductivity of 78.8-85.6% IACS.

[0060] Example 1

[0061] A method for preparing a copper heat dissipation material by electrolytic copper powder injection molding, the method for preparing a copper heat dissipation material by electrolytic copper powder injection molding comprises the following steps:

[0062] S1. Grinding and crushing of electrolytic copper powder: 5 kg of 500-mesh electrolytic copper powder was weighed and crushed into powder particles by mechanical impact grinding. The mill speed of the ultrafine mechanical impact mill was set to 2500 r / min, the classification impeller speed was 1500 r / min, and the feed rate was 200 g / min. After 3 hours of high-speed powder treatment, 2 kg of 10-15 μm electrolytic copper powder was screened out;

[0063] S2, powder mixing: 2kg of the electrolytic copper powder ground from S1, 1.5% of ZrCuAlNi alloy powder and an injection molding binder (microcrystalline wax with a mass fraction of 60%, polyethylene with a mass fraction of 15%, polypropylene with a mass fraction of 10%, ethylene-vinyl acetate copolymer with a mass fraction of 10%, and vinyl bisstearamide with a mass fraction of 5%) were mixed in a volume ratio of 1:1, and mixed at 165°C and 30r / min for 60min. Argon was selected as the protective atmosphere for the mixing to obtain a high-purity feed;

[0064] Solvent degreasing and thermal degreasing were used to obtain the samples after thermal degreasing. During the injection process, the injection temperature was 160℃, the injection pressure was 60bar, the injection speed was 50mm / s, and the mold temperature was 65℃. The main component of the binder removed by solvent degreasing was microcrystalline wax. When thermal degreasing was performed from room temperature to 500℃, the heating rate was 1.5℃ / min, and the samples were kept at 250℃, 380℃, and 500℃ for 30min respectively. The degreasing rate of the sample after thermal degreasing was 6.8%, and the density was 4.82g / cm 3 ;

[0065] S4, atmospheric pressure sintering + aging treatment + pressure sintering: The sample after S3 thermal stripping was subjected to hydrogen atmosphere atmospheric pressure sintering, solution aging treatment and pressure sintering in sequence. In the atmospheric pressure sintering step, the flow rate of the hydrogen introduced was 3.0 m / s. 3 / min, heat up to 500℃ at a rate of 1℃ / min, then heat up to 1070℃ at a rate of 2℃ / min, and then keep warm for 150min; then cool down to room temperature with the furnace, and then carry out aging treatment, the aging temperature is 120℃, the aging time is 40h, and during pressure sintering, keep warm at 1030℃ under 5bar pressure for 3h in a nitrogen atmosphere.

[0066] S5, annealing: the copper heat sink material after sintering in S4 is annealed at 550°C, kept at this temperature for 60 minutes, and then cooled in a hydrogen atmosphere to obtain a defect-free and deformation-free heat sink sample.

[0067] like Figure 2 As shown, the shape of the heat sink sample prepared in this embodiment is a needle-column-shaped heat sink with a high specific surface area, and the microstructure is as follows Figure 3 As shown; in terms of performance, the density is 98.6%, the hardness is 123HV, the tensile strength is 301.6MPa, the elongation is 28.2%, the thermal conductivity is 359W / (m·K), and the electrical conductivity is 82.3%IACS.

[0068] Comparative Example 1 is Chinese patent CN114131018A, which discloses a method for preparing a pressed copper nano-stacked bed heat dissipation material. The method requires the use of four mixed particles, an arrangement method and a copper mesh structure setting, and cold pressing and vacuum sintering make the prepared heat dissipation material a porous structure material. The method can simplify the production process, reduce the difficulty of the preparation process and the requirements for instrument accuracy; the prepared heat dissipation material can be used in phase change heat transfer, can have excellent phase change heat transfer performance, and can greatly improve the cooling efficiency of electronic devices.

[0069] By comparing Example 1 with Comparative Example 1, it can be seen that simply mixing multiple powders has the effect of dispersing and strengthening copper, which greatly improves the yield strength of the material, but the electrical conductivity of the material is poor, and the thermal conductivity of each part is not uniform. The present invention maximizes the distribution uniformity between powder particles by solid solution reaction with alloy powder after electrolytic powder treatment, and then performs aging treatment after subsequent sintering, and then achieves full sintering density through pressure sintering. While ensuring the excellent thermal and electrical conductivity of copper, the mechanical properties of the material such as strength and hardness are also greatly improved.

[0070] Example 2

[0071] A method for preparing a copper heat dissipation material by electrolytic copper powder injection molding, the method for preparing a copper heat dissipation material by electrolytic copper powder injection molding comprises the following steps:

[0072] S1. Grinding and crushing of electrolytic copper powder: 5 kg of 500-mesh electrolytic copper powder was weighed and crushed into powder particles by mechanical impact grinding. The mill speed of the ultrafine mechanical impact mill was set to 2500 r / min, the classification impeller speed was 1500 r / min, and the feed rate was 200 g / min. After 3 hours of high-speed powder treatment, 2 kg of 10-15 μm electrolytic copper powder was screened out;

[0073] S2, powder mixing: 3kg of ground electrolytic copper powder of S1, 1.8% ZrCuAlNi alloy powder and injection molding binder (microcrystalline wax mass fraction of 65%, polyethylene mass fraction of 15%, polypropylene mass fraction of 8%, ethylene-vinyl acetate copolymer mass fraction of 8%, vinyl bisstearamide mass fraction of 4%), are mixed in a volume ratio of 55:45, and mixed at 160°C and 25r / min for 80min. Argon is selected as the protective atmosphere in the mixing atmosphere to obtain high-purity feed;

[0074] S3, injection molding: high-purity feed is used to inject molding using an injection molding machine and a matching mold to obtain a defect-free, deformation-free, uniform composition radiator green body; then the radiator green body is solvent degreased and heated to obtain a thermally degreased sample; during the injection process, the injection temperature is 165°C, the injection pressure is 65 bar, the injection speed is 55 mm / s, and the mold temperature is 60°C; the main component of the binder removed by solvent degreasing is microcrystalline wax; thermal degreasing is when the temperature is increased from room temperature to 500°C, the heating rate is 1°C / min, and the temperature is kept at 200°C, 30°C, and 450°C for 30 minutes respectively. The degreasing rate of the sample after thermal degreasing is 7.0%, and the density is 5.01g / cm 3 .

[0075] S4, atmospheric pressure sintering + aging treatment + pressure sintering: The sample after thermal stripping in S3 was subjected to hydrogen atmosphere atmospheric pressure sintering, solution aging treatment and pressure sintering in sequence. In the atmospheric pressure sintering step, the flow rate of the hydrogen introduced was 3.5m / s. 3 / min, heat up to 500℃ at a rate of 1℃ / min, then heat up to 1070℃ at a rate of 1.5℃ / min, and then keep warm for 220min; then cool down to room temperature with the furnace, and then carry out aging treatment, the aging temperature is 130℃, the aging time is 35h, and during pressure sintering, in a nitrogen atmosphere, under a pressure of 10bar, keep warm at 1040℃ for 2h.

[0076] S5, annealing: the copper heat sink material after sintering in S4 is annealed at 600°C, kept at this temperature for 50 minutes, and then cooled in a hydrogen atmosphere to obtain a defect-free and deformation-free heat sink sample.

[0077] The shape of the heat sink sample prepared in this embodiment is a needle-column-shaped high specific surface area heat sink. In terms of performance, the density is 98.4%, the hardness is 121HV, the tensile strength is 295.9MPa, the elongation is 26.8%, the thermal conductivity is 356W / (m·K), and the electrical conductivity is 80.1%IACS.

[0078] Example 3

[0079] A method for preparing a copper heat dissipation material by electrolytic copper powder injection molding, the method for preparing a copper heat dissipation material by electrolytic copper powder injection molding comprises the following steps:

[0080] S1. Grinding and crushing of electrolytic copper powder: 5 kg of 500-mesh electrolytic copper powder was weighed and crushed into powder particles by mechanical impact grinding. The mill speed of the ultrafine mechanical impact mill was set to 2000 r / min, the classification impeller speed was 1200 r / min, and the feed rate was 180 g / min. After 2.5 h of high-speed powder treatment, 2.5 kg of 10-15 μm electrolytic copper powder was screened out;

[0081] S2, powder mixing: 2kg of the ground electrolytic copper powder of S1, 1.8% of ZrCuAlNi alloy powder and injection molding binder (microcrystalline wax mass fraction of 70%, polyethylene mass fraction of 10%, polypropylene mass fraction of 8%, ethylene-vinyl acetate copolymer mass fraction of 7%, vinyl bisstearamide mass fraction of 5%), are mixed in a volume ratio of 3:2, and mixed at 155°C and 35r / min for 60min. Nitrogen is selected as the protective atmosphere in the mixing atmosphere to obtain high-purity feed;

[0082] S3, injection molding: high-purity feed is used to inject molding using an injection molding machine and a matching mold to obtain a defect-free, deformation-free, uniform composition radiator green body; then the radiator green body is solvent degreased and heated to obtain a thermally degreased sample; during the injection process, the injection temperature is 155°C, the injection pressure is 70 bar, the injection speed is 40 mm / s, and the mold temperature is 55°C; the main component of the binder removed by solvent degreasing is microcrystalline wax; thermal degreasing is when the temperature rises from room temperature to 450°C for degreasing, the heating rate is 1.5°C / min, and the temperature is kept at 220°C, 310°C, and 450°C for 30 minutes respectively. The degreasing rate of the sample after thermal degreasing is 7.2%, and the density is 5.10g / cm 3 .

[0083] S4, atmospheric pressure sintering + aging treatment + pressure sintering: The sample after thermal stripping in S3 was subjected to hydrogen atmosphere atmospheric pressure sintering, solution aging treatment and pressure sintering in sequence. In the atmospheric pressure sintering step, the flow rate of the hydrogen introduced was 3.8 m / s. 3 / min, heat up to 500℃ at a rate of 2℃ / min, then heat up to 1070℃ at a rate of 1.5℃ / min, and then keep warm for 250min; then cool down to room temperature with the furnace, and then carry out aging treatment, the aging temperature is 115℃, the aging time is 45h, and during pressure sintering, in a nitrogen atmosphere, under a pressure of 12bar, keep warm at 1050℃ for 2.5h.

[0084] S5, annealing: the copper heat sink material after sintering in S4 is annealed at 580°C, kept at this temperature for 75 minutes, and then cooled in a hydrogen atmosphere to obtain a defect-free and deformation-free heat sink sample.

[0085] The shape of the heat sink sample prepared in this embodiment is a needle-column-shaped high specific surface area heat sink. In terms of performance, the density is 99.1%, the hardness is 131HV, the tensile strength is 315.4MPa, the elongation is 26.9%, the thermal conductivity is 362W / (m·K), and the electrical conductivity is 84.6%IACS.

[0086] Example 4

[0087] A method for preparing a copper heat dissipation material by electrolytic copper powder injection molding, the method for preparing a copper heat dissipation material by electrolytic copper powder injection molding comprises the following steps:

[0088] S1. Grinding and crushing of electrolytic copper powder: 5 kg of 500-mesh electrolytic copper powder was weighed and crushed into powder particles by mechanical impact grinding. The mill speed of the ultrafine mechanical impact mill was set to 2300 r / min, the classification impeller speed was 1300 r / min, and the feed rate was 150 g / min. After 3 hours of high-speed powder treatment, 3 kg of 10-15 µm electrolytic copper powder was screened out;

[0089] S2, powder mixing: 3kg of the ground electrolytic copper powder of S1 and 2.2% of the ZrCuAlNi alloy powder injection molding binder (microcrystalline wax mass fraction of 60%, polyethylene mass fraction of 21%, polypropylene mass fraction of 12%, ethylene-vinyl acetate copolymer mass fraction of 6%, vinyl bisstearamide mass fraction of 1%) are mixed in a volume ratio of 58:42, and mixed at 158°C and 28r / min for 80min. Nitrogen is selected as the protective atmosphere in the mixing atmosphere to obtain high-purity feed;

[0090] S3, injection molding: high-purity feed is used to inject molding using an injection molding machine and a matching mold to obtain a defect-free, deformation-free, uniform composition radiator green body; then the radiator green body is subjected to catalytic degreasing and thermal degreasing to obtain a thermally degreased sample; during the injection process, the injection temperature is 158°C, the injection pressure is 65 bar, the injection speed is 35 mm / s, and the mold temperature is 50°C; the main component of the binder removed by solvent degreasing is microcrystalline wax; thermal degreasing is when the temperature is increased from room temperature to 500°C, the heating rate is 1.8°C / min, and the temperature is kept at 240°C, 320°C, and 480°C for 30 minutes respectively. The degreasing rate of the sample after thermal degreasing is 6.6%, and the density is 4.73g / cm 3 .

[0091] S4, atmospheric pressure sintering + aging treatment + pressure sintering: The sample after thermal stripping in S3 was subjected to hydrogen atmosphere atmospheric pressure sintering, solution aging treatment and pressure sintering in sequence. In the atmospheric pressure sintering step, the flow rate of the hydrogen introduced was 2.8 m / s. 3 / min, heat up to 500℃ at a rate of 1℃ / min, then heat up to 1070℃ at a rate of 1.8℃ / min, and then keep warm for 240min; then cool down to room temperature with the furnace, and then carry out aging treatment, the aging temperature is 110℃, the aging time is 30h, and during pressure sintering, in a nitrogen atmosphere, at a pressure of 15bar, keep warm at 1010℃ for 2h.

[0092] S5, annealing: the copper heat sink material after sintering in S4 is annealed at 610°C, kept at this temperature for 50 minutes, and then cooled in a hydrogen atmosphere to obtain a defect-free and deformation-free heat sink sample.

[0093] The shape of the heat sink sample prepared in this embodiment is a needle-column-shaped high specific surface area heat sink. In terms of performance, the density is 98.2%, the hardness is 105HV, the tensile strength is 288.6MPa, the elongation is 25.5%, the thermal conductivity is 352W / (m·K), and the electrical conductivity is 78.8%IACS.

[0094] Example 5

[0095] A method for preparing a copper heat dissipation material by electrolytic copper powder injection molding, the method for preparing a copper heat dissipation material by electrolytic copper powder injection molding comprises the following steps:

[0096] S1. Grinding and crushing of electrolytic copper powder: 5 kg of 500-mesh electrolytic copper powder was weighed and crushed into powder particles by mechanical impact grinding. The mill speed of the ultrafine mechanical impact mill was set to 3000 r / min, the classification impeller speed was 1800 r / min, and the feed rate was 220 g / min. After 3 hours of high-speed powder treatment, 3 kg of 10-15 μm electrolytic copper powder was screened out;

[0097] S2, powder mixing: 3kg of the ground electrolytic copper powder of S1, 2.5% of ZrCuAlNi alloy powder and injection molding binder (microcrystalline wax mass fraction of 55%, polyethylene mass fraction of 15%, polypropylene mass fraction of 12%, ethylene-vinyl acetate copolymer mass fraction of 12%, vinyl bisstearamide mass fraction of 6%), are mixed in a volume ratio of 58:42, and mixed at 163°C and 40r / min for 60min. Argon is selected as the protective atmosphere of the mixing atmosphere to obtain high-purity feed;

[0098] S3, injection molding: high-purity feed is used to inject molding using an injection molding machine and a matching mold to obtain a defect-free, deformation-free, uniform composition radiator green body; then the radiator green body is subjected to catalytic degreasing and thermal degreasing to obtain a thermally degreased sample; during the injection process, the injection temperature is 163°C, the injection pressure is 70 bar, the injection speed is 60 mm / s, and the mold temperature is 56°C; the main component of the binder removed by solvent degreasing is microcrystalline wax; thermal degreasing is when the temperature is increased from room temperature to 500°C, the heating rate is 1.2°C / min, and the temperature is kept at 220°C, 350°C, and 500°C for 30 minutes respectively. The degreasing rate of the sample after thermal degreasing is 7.8%, and the density is 5.10g / cm 3 .

[0099] S4, atmospheric pressure sintering + aging treatment + pressure sintering: The sample after thermal stripping in S3 was subjected to hydrogen atmosphere atmospheric pressure sintering, solution aging treatment and pressure sintering in sequence. In the atmospheric pressure sintering step, the flow rate of the hydrogen introduced was 4.2 m / s. 3 / min, heat up to 500℃ at a rate of 1℃ / min, then heat up to 1075℃ at a rate of 1.2℃ / min, and then keep warm for 300min; then cool down to room temperature with the furnace, and then carry out aging treatment, the aging temperature is 120℃, the aging time is 40h, and during pressure sintering, in a nitrogen atmosphere, at a pressure of 15bar, keep warm at 1050℃ for 3h.

[0100] S5, annealing: the copper heat sink material after sintering in S4 is annealed at 650°C, kept at this temperature for 80 minutes, and then cooled in a hydrogen atmosphere to obtain a defect-free and deformation-free heat sink sample.

[0101] The shape of the heat sink sample prepared in this embodiment is a needle-column-shaped high specific surface area heat sink. In terms of performance, the density is 99.5%, the hardness is 146HV, the tensile strength is 325.2MPa, the elongation is 34.2%, the thermal conductivity is 367W / (m·K), and the electrical conductivity is 85.6%IACS.

[0102] Example 6

[0103] A method for preparing a copper heat dissipation material by electrolytic copper powder injection molding, the method for preparing a copper heat dissipation material by electrolytic copper powder injection molding comprises the following steps:

[0104] S1. Grinding and crushing of electrolytic copper powder: 5 kg of 500-mesh electrolytic copper powder was weighed and crushed into powder particles by mechanical impact grinding. The mill speed of the ultrafine mechanical impact mill was set to 2200 r / min, the classification impeller speed was 1300 r / min, and the feed rate was 160 g / min. After 3 hours of high-speed powder treatment, 2.5 kg of 10-15 μm electrolytic copper powder was screened out;

[0105] S2, powder mixing: 2.5 kg of the electrolytic copper powder ground from S1, 1.5% of the ZrCuAlNi alloy powder and an injection molding binder (microcrystalline wax with a mass fraction of 60%, polyethylene with a mass fraction of 18%, polypropylene with a mass fraction of 8%, ethylene-vinyl acetate copolymer with a mass fraction of 8%, and vinyl bisstearamide with a mass fraction of 6%) were mixed in a volume ratio of 55:45, and mixed at 155°C and 30 r / min for 60 min. Argon was selected as the protective atmosphere for the mixing to obtain a high-purity feed;

[0106] S3, injection molding: high-purity feed is used to inject molding using an injection molding machine and a matching mold to obtain a defect-free, deformation-free, uniform composition radiator green body; then the radiator green body is subjected to catalytic degreasing and thermal degreasing to obtain a thermally degreased sample; during the injection process, the injection temperature is 155°C, the injection pressure is 55 bar, the injection speed is 40 mm / s, and the mold temperature is 50°C; the main component of the binder removed by solvent degreasing is microcrystalline wax; thermal degreasing is when the temperature is increased from room temperature to 480°C for degreasing, the heating rate is 1.5°C / min, and the temperature is kept at 200°C, 320°C, and 480°C for 30 minutes respectively. The degreasing rate of the sample after thermal degreasing is 6.9%, and the density is 4.96g / cm 3 .

[0107] S4, atmospheric pressure sintering + aging treatment + pressure sintering: The sample after thermal stripping in S3 was subjected to hydrogen atmosphere atmospheric pressure sintering, solution aging treatment and pressure sintering in sequence. In the atmospheric pressure sintering step, the flow rate of the hydrogen introduced was 3.5m / s. 3 / min, and then heated to 500℃ at a rate of 1.5℃ / min, and then heated to 1065℃ at a rate of 2.5℃ / min after 500℃, and then kept warm for 180min; then cooled to room temperature with the furnace, and then aging treatment was carried out, the aging temperature was 125℃, and the aging time was 40h. During pressure sintering, in a nitrogen atmosphere, the temperature was kept at 1030℃ at a pressure of 8bar for 3h;

[0108] S5, annealing: the copper heat sink material after sintering in S4 is annealed at 630°C, kept at this temperature for 80 minutes, and then cooled in a hydrogen atmosphere to obtain a defect-free and deformation-free heat sink sample.

[0109] The shape of the heat sink sample prepared in this embodiment is a needle-column-shaped high specific surface area heat sink. In terms of performance, the density is 98.8%, the hardness is 126HV, the tensile strength is 295.5MPa, the elongation is 29.3%, the thermal conductivity is 362W / (m·K), and the electrical conductivity is 83.4%IACS.

[0110] The above scheme, the present invention proposes a method for preparing copper heat dissipation materials by electrolytic copper powder injection molding, which can solve the problems of low utilization rate of heat dissipation materials in the prior art, complex structure and difficulty in preparation, and high production cost. If alloy particles are added to improve thermal conductivity and electrical conductivity, there will be technical problems such as the performance of the two cannot be improved synergistically, accompanied by mismatch of strength and plasticity, inability to prepare complex-shaped copper parts, and difficulty in operation.

[0111] The preparation method of the present invention prevents the high activity and easy oxidation of copper, realizes the sintering activation effect of electrolytic copper powder and the liquid phase sintering effect of low-melting copper-nickel powder, the high shape retention of plastic-based system samples and the high degreasing rate of green billets, and also adopts a variety of mechanisms to promote sintering densification, such as hydrogen atmosphere sintering and hot isostatic pressing sintering, which can significantly improve sintering densification.

[0112] The present invention uses a grinding and crushing process to disperse the agglomerated particles by utilizing the impact force generated when the particles collide with each other, and the edges and corners of the particle surfaces are ground off due to the mutual friction between the particles, so that the particle surfaces are smoother and more regular, thereby obtaining spherical or nearly spherical particles. Nearly spherical particles are more easily coated by binder particles, thereby greatly increasing the loading amount of the powder, making the density of the sintered product higher, thereby improving its thermal conductivity, electrical conductivity and mechanical properties.

[0113] The present invention enables the feed material to have good flowability through the selection of the wax-based binder, can meet the requirements of rapid prototyping of large-sized complex parts in the subsequent injection process, and can manufacture products with complex shapes and high precision requirements.

[0114] The present invention can integrate parts with complex structures through injection molding, with almost no material loss and a utilization rate of up to 98%, solving the problems of low utilization rate of radiator machining materials, complex and difficult preparation, and high production cost, and provides a new idea for the preparation of heat dissipation devices with high material costs and complex structures.

[0115] The present invention uses normal pressure sintering + aging treatment + pressure sintering to ensure that the strength-enhancing grains are fully grown and the grains are closely combined. After the solid solution aging treatment, the alloy elements form a dispersed strengthening phase in the matrix, which can significantly improve its tensile strength and ductility. Solid solution aging can refine the grains, reduce the stress concentration at the grain boundaries, make the material less likely to brittle fracture when subjected to external forces, and improve the service life of the product. The heat dissipation product may be deformed due to residual stress during subsequent processing. Solid solution aging treatment can also make the part size more stable by eliminating or reducing residual stress. For some copper alloy products, solid solution aging treatment can make the impurity elements evenly distributed, reduce lattice distortion, and thus improve the thermal conductivity and electrical conductivity of the alloy. This is of great significance in heat dissipation materials, and can make the electrical conductivity of electronic components better and reduce power loss. The sintered parts are basically fully dense, and excellent comprehensive performance is obtained to meet the use requirements of the radiator.

[0116] The present invention eliminates residual stress by performing stress relief annealing on the sintered part. Stress relief annealing can make the material's organizational structure more uniform, improve dimensional stability, and prevent the workpiece from deforming during subsequent use, ultimately obtaining a copper heat dissipation material with high strength, high thermal conductivity and excellent ductility.

[0117] The copper heat dissipation material prepared by the present invention has a density of more than 98.2%, a thermal conductivity of ≥352W / (m·K), an electrical conductivity of up to 85.6% IACS, and has excellent thermal and electrical conductivity. The copper sample has an elongation of up to 34.2%, a tensile strength of 325.2MPa, good ductility and tensile strength, is not prone to fracture and damage, and can meet the performance requirements of high thermal conductivity complex structure copper heat sinks.

[0118] In summary, compared with other traditional methods, the method of the present invention realizes the preparation of integrated needle-shaped heat dissipation materials through various mechanisms that promote sintering densification, such as powder particle size control and micro-shaping, atmosphere protection mixing, activated sintering, solution aging treatment, pressure sintering, and stress relief annealing treatment. The thermal conductivity, electrical conductivity, and strength and plasticity of the copper heat dissipation material are synergistically improved. The method is simple and easy to operate, green and environmentally friendly, low in cost, short in process, and high in efficiency. It meets the preparation requirements of high thermal conductivity, large-size, complex-structure copper heat dissipation materials, and is conducive to large-scale industrial production and promotion.

[0119] It should be understood that the term "and / or" in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship, but it may also indicate an "and / or" relationship. Please refer to the context for specific understanding.

[0120] In the present invention, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, at least one of a, b, or c can mean: a, b, c, ab, ac, bc, or abc, where a, b, and c can be single or multiple.

[0121] It should be understood that in various embodiments of the present invention, the size of the serial numbers of the above-mentioned processes does not mean the order of execution. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present invention.

[0122] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for preparing copper heat dissipation material by electrolytic copper powder injection molding, characterized in that: The method for preparing copper heat dissipation material by electrolytic copper powder injection molding is as follows: S1. Grinding and crushing of electrolytic copper powder: weighing electrolytic copper powder, crushing the electrolytic copper powder particles by ultrafine mechanical impact mill, and obtaining ground and crushed electrolytic copper powder; S2, powder mixing: the electrolytic copper powder and alloy powder ground and crushed in S1 are mixed with wax-based binder at high temperature and high speed to obtain high-purity feed; S3, injection molding: S2 high-purity feed is injection molded to obtain a green part with no defects, no deformation and uniform composition; then the green part is subjected to catalytic degreasing and thermal degreasing to obtain a thermally degreased sample; S4, normal pressure sintering + aging treatment + hot isostatic pressing sintering: the sample after thermal stripping in S3 is subjected to normal pressure sintering in hydrogen atmosphere + aging treatment + pressure sintering in nitrogen atmosphere in sequence to obtain the sintered copper heat dissipation material; S5, annealing: The copper heat dissipation material after sintering in S4 is subjected to stress relief annealing to finally obtain a copper heat dissipation material with high strength, high thermal conductivity and excellent ductility.

2. The method for preparing copper heat dissipation material by electrolytic copper powder injection molding according to claim 1, characterized in that: The particle size D50 of S1 electrolytic copper powder is 15-20µm.

3. The method for preparing copper heat dissipation material by electrolytic copper powder injection molding according to claim 1, characterized in that: The experimental parameters of S1 ultrafine mechanical impact mill are: inlet air volume 200-300m 3 / h, mill speed 2500-3000r / min, classification impeller speed 1500-2500r / min, feed rate 100-200g / min, after 2-4h of high-speed powder treatment, 10-15µm powder is screened out, the alloy powder is ZrCuAlNi, and its mass fraction is 1.5-3.0%.

4. The method for preparing copper heat dissipation material by electrolytic copper powder injection molding according to claim 1, characterized in that: The mass fraction of microcrystalline wax in the wax-based binder in S2 is 50-70%, the mass fraction of polyethylene is 15-25%, the mass fraction of polypropylene is 10-15%, the mass fraction of ethylene-vinyl acetate copolymer is 10-15%, and the mass fraction of vinyl bisstearamide is 5-10%; argon or nitrogen is selected as the protective atmosphere for the mixing atmosphere.

5. The method for preparing copper heat dissipation material by electrolytic copper powder injection molding according to claim 1, characterized in that: The temperature of S2 high temperature and high speed internal mixing is 150-170°C, the speed of the internal mixer is 25-40rpm, and the internal mixing time is 1-2h.

6. The method for preparing copper heat dissipation material by electrolytic copper powder injection molding according to claim 1, characterized in that: During the S3 injection process, the injection temperature is 150-170℃, the injection pressure is 40-80bar, the injection speed is 40-60mm / s, and the mold temperature is 50-75℃; the main component of the binder removed by solvent degreasing is microcrystalline wax; when thermal degreasing is performed from room temperature to 500℃, the heating rate is 1℃ / min, and the temperatures are kept at 250℃, 380℃, and 550℃ for 30min respectively.

7. The method for preparing copper heat dissipation material by electrolytic copper powder injection molding according to claim 1, characterized in that: S3 solvent degreasing uses trichloroethylene for solvent degreasing, dissolving at 40-55℃ for 15-30h to remove the main component of microcrystalline wax in the binder.

8. The method for preparing copper heat dissipation material by electrolytic copper powder injection molding according to claim 1, characterized in that: The degreasing rate of the S3 samples after thermal degreasing is 6.0-7.8%, and the density is 4.55-5.10g / cm 3 .

9. The method for preparing copper heat dissipation material by electrolytic copper powder injection molding according to claim 1, characterized in that: In the step of S4 atmospheric pressure sintering, the flow rate of the hydrogen gas is ≥ 3m 3 / min, sintering temperature is 1065-1075℃, and holding time is 3-5h; during aging treatment, the aging temperature is 110-140℃, and the aging time is 30-50h. During pressure sintering, in a nitrogen atmosphere, at a pressure of 5-15bar, keep warm at a temperature of 1000-1050℃ for 2-4h.

10. The method for preparing copper heat dissipation material by electrolytic copper powder injection molding according to claim 1, characterized in that: In S5, the annealing treatment is carried out at 500-650° C., and the temperature is kept at this temperature for 45-80 minutes, followed by furnace cooling in a hydrogen atmosphere.

Citation Information

Patent Citations

  • Method for preparing high-thermal-conductivity and high-temperature-resistant composite copper alloy heat dissipation material

    CN111455373A

  • Preparation method of copper-based metal honeycomb heat dissipation material

    CN113458396A

  • Preparation method of net pressing copper nanometer packed bed heat dissipation material

    CN114131018A

  • Nano-porous copper heat dissipation material based on composite copper mesh and surface modification combination and preparation method of nano-porous copper heat dissipation material

    CN118926519A

  • Method for preparing radiator element with complicated shape

    CN101520287A